Bingkai Media pada Program Acara Televisi Satu Indonesia Net.tv Episode Sultan HB X dan Asia Calling Tempo Tv Episode Penerus Tahta Raja Yogyakarta - Sigit Surahman (Nyimak: Journal of Communication, 2018)
Yogyakarta menganut kekuasaan monarki yang keberadaannya diatur dalam UU No. 13 tahun 2012 yang mengharuskan Gubernur adalah Raja Keraton Yogyakarta. Sri Sultan HB X mengeluarkan Sabda Raja yang mengangkat GKR Pambayun menjadi Putri Mahkota untuk mempersiapkan penerus tahta. Seharusnya yang menjadi penerus tahta raja adalah salah satu dari adik Sri Sultan HB X. Muncul pertanyaan berikut: Bagaimana bingkai media program acara satu Indonesia Net.tv “eps” Sultan HB X dan asia calling Tempo Tv “eps” penerus tahta raja Yogyakarta?, Apa bukti hegemoni Sri Sultan HB X?, Bagaimana topik berita yang sesuai dengan apa yang disampaikan Sultan HB X? Sultan HB X ingin mempertahankan kelanggengan kekuasaan. Framing is a multi-layered concept. It can operate individually, on the micro level, in terms of how citizens frame political issues. This has been the focus of the discussion up to this point. Framing can also operate on a macro level (Perloff, 2014:165). Hegemony, the notion that political leaders can enforce their will on the Mass public by manufacturing consent, harnessing mass communications in the Service of their political objectives (Perloff, 2014:166). Indexing, the idea that political media index news so that it closely matches the range of voices expressed by political elites (Bennett, 1994; Bennett, Lawrence, & Livingston, 2006: Perloff, 2014:166). Penelitian kualitatif deskrtiptif relevan untuk memperoleh informasi lengkap mengenai hegemoni Sri Sultan HB X.Kata Kunci: Bingkai, sabda raja, putri mahkota Yogyakarta embraces the monarchical power whose existence is regulated in Law no. 13 of 2012 which requires the Governor is the King of Yogyakarta Palace. Sri Sultan HB X issued the King's Word which elevated GKR Pambayun to Crown Princess to prepare the successor to the throne. Should be the successor to the throne of the king is one of Sri Sultan HB X's sister. The following questions arise: How to frame the media of the event program one Indonesia Net.tv "eps" Sultan HB X and asia calling Tempo Tv "eps" successor to the throne of the king of Yogyakarta ?, What is the evidence of the hegemony of Sri Sultan HB X ?, How do the news topics match what Sultan HB X has to say? Sultan HB X wants to maintain the continuity of power. Framing is a multi-layered concept. It can operate individually, on the micro level, in terms of how citizens frame political issues. This has been the focus of the discussion up to this point. Framing can also operate on a macro level (Perloff, 2014: 165). Hegemony, the notion that political leaders can enforce their will on the Mass public by manufacturing consent, harnessing mass communications in the Service of their political objectives (Perloff, 2014: 166). Indexing, the idea that political media index news so that it closely matches the range of voices expressed by political elites (Bennett, 1994; Bennett, Lawrence, & Livingston, 2006: Perloff, 2014: 166). Descriptive qualitative research is relevant to obtain complete information about the hegemony of Sri Sultan HB X.Keywords: Frame, king's word, crown princess